The Influence of Work Stress, Work Load and Work Environment on Turnover Inten-tion Employees of PT Jayamandiri Cirebon - Tinjung Desy Nursanti; Vestika Astri Lianto; Kievlan Azzam Venir; Lilis Mardiyah (Jurnal Ilmu Manajemen & Ekonomika, 2022)
The aim of this study is to determine the effect of work stress, work load, and work environment on turno-ver intention at PT Jayamandiri Cirebon. The method in this study uses quantitative methods. Data collec-tion techniques through questionnaires distributed to 43 respondents. The data analysis technique used multiple linear regression analysis. The results of the study indicate that work stress and work load have a significant and positive effect on turnover intention. While the work environment variable does not have a significant relationship to turnover intention, however if they have a better work environment, employees will be more comfortable and able to carry out their work to the fullest. Simultaneously the variables of work stress, work load, and work environment have a significant effect on turnover intention. This means that the influence made on this workload factor which includes targets to be achieved, working conditions, use of time and work standards must be considered again so that employees will feel more comfortable and do not feel burdened with work, thus enabling them to carry out their work maximally.